The influence of wind and the spatial layout of dwellings on fire spread in informal settlements in Cape Town. (January 2022) - Gibson, Lesley; Cicione, Antonio; Stevens, Samuel; Rush, David
Abstract: Fires in informal settlements are devastating to residents of these precarious urban environments. This paper highlights the use of spatial metrics and wind speed and direction for fire spread risk identification for informal settlement fires in Cape Town. Data on: fire incidents, dwelling footprints, and the wind conditions during a fire, are analysed both together and separately. Fire incidence data analysed with wind data reveals that the majority of fires occur in December with the most destructive fires taking place during moderate wind conditions. At higher wind speeds, the distance between the flame and adjacent dwelling is not reduced but the flame height is, leading to reduced radiation. Also, convective cooling at higher wind speeds increases the time-to-ignition and flashover of the adjacent dwelling. Analysis of dwelling data reveals that the average and standard deviation of distance to the first nearest neighbour together with edge density can be used to identify areas at risk of fire spread. A threshold approach using the distance to a dwelling's first nearest neighbour together with the range in distance from the dwelling's first to third nearest neighbours allow for the identification of specific dwellings within a settlement which are at risk of fire spread. Highlights: Fires mapped from Sentinel-2 data used to extract spatial metrics of fire spread risk. Spatial metrics in combination can identify areas at high risk of fire spread. Large fires are generally associated wind speed of 3 to 8 m.s −1 .